Compleción del modelo del overshooting de Dornsbusch - García-Cobián Jáuregui, Ramón (2005)
The article tries to complete the “overshooting” model of Dornsbusch, explicitly including a dynamic equation for the money market, because he treats this only in an intuitive way, as if there was an infinite speed of adjustment. After pointing out some errors in the original work, it is showed that the hypotheses made by Dornsbusch are sufficient for the completed model to exhibit the wanted “overshooting”.